The Influence of Product and Service Quality on Coffee Shop Entrance Fees: An Application of Hedonic Price Theory - จั่นจินดา, จุฑารัตน์; กิติเวียง, รมยพร; ขันทะวงค์, พรชัย; เดชจิรมณี, ชัชชติภัช; พิพัฒน์พงศ์อำไพ, อาทิตยา; ประวิตรางกูร, ศรัณย์ (วารสารนวัตกรรมธุรกิจ การจัดการ และสังคมศาสตร์, 2024)
The purpose of this research was to study factors affecting coffee shop entrance fees according to the characteristics of the coffee shop. This research applied hedonic pricing theory to determine entrance fees of coffee shops, which were location, product characteristics, and service. The secondary data was retrieved from Facebook and Google Maps business information of 134 coffee shops in tourist towns in Thailand. The data was analyzed by regression analysis. The research found that factors determining entrance fees were consistent and statistically significant with the theory, especially the mountain view, and the redemption of entrance fees for products. However, the social media factors, Facebook followers, and Google Maps ratings were not significant to entrance fees, which implies that there was a problem with the quality of followers and rating of coffee shops.